ANALISIS LAPORAN ARUS KAS PADA PT. UNILEVER INDONESIA TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Shaqinah, Azalika Putri; Mulatsih, Endang Sri; Kurniati, Echi; Jannah, Miftahul; Feriyana, Winda (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this study was to compare the cash flow statements for each operating, funding, and investing activity at PT. Unilever Indonesia Tbk for the years 2018–2022. It also sought to ascertain how the cash flow statement's performance at PT. Unilever Indonesia Tbk for the same period was perceived using cash flow ratio analysis. The financial statements for the years 2018 through 2022 of PT. Unilever Indonesia tbk are the subject of this study, which has its locus at that company. The descriptive approach of data analysis is employed in conjunction with qualitative research methods. The study's findings show that because revenue surpasses expenses, the company's operating cash flow is positive from 2018 to 2022. However, because cash from operations is utilized to pay dividends, investments, and loans, finance and investment activities typically result in negative outcomes. The company's ability to cover interest charges varies with a ratio of 78%, while its ability to pay current liabilities with operational cash flow is just 64%. Cash coverage to current debt varies as well; it can be as high as 111%, yet the capital expenditure ratio is as low as 105%. The cash flow to total debt ratio is erratic at 59%, and over the next five years, it will be 42% for the cash flow adequacy ratio. Keywords: Analysis of cash flow ratios and cash flow statements